Price, Promotion, and Online Customer Ratings: Factors Determining the Purchase Decisions for Sheona Go Fashion Products on E-Commerce - Pandiangan, Sari Yanti; Herlina, Listri; Akbar, Ridho Riadi (Training & Research Institute - Jeramba Ilmu Sukses, 2025)
Along with the increasing popularity of online fashion shopping, this study aims to analyze the influence of price, promotion, and online customer ratings on purchasing decisions for Sheona Go fashion products on the E-Commerce platform. This study is important to understand the factors influencing online shopping behavior. The research method used is a quantitative approach with a survey. Using a purposive sampling technique, data were collected from 100 respondents who had purchased Sheona Go products through the E-Commerce platform. The variables studied include price, promotion, and online customer ratings as independent variables and purchasing decisions as dependent variables. The results of the analysis show that simultaneously, price, promotion, and online customer ratings have a significant effect on purchasing decisions. Partially, the price variable has the most dominant influence, followed by promotion and online customer ratings. Descriptive statistics show that most respondents positively assessed price and promotion, while perceptions of online customer ratings were more varied. These findings provide insights for online fashion business players in designing more effective marketing strategies and the importance of maintaining digital reputation and optimizing customer experience on online platforms. This study also strengthens the theory of Consumer Behavior in the context of E-Commerce.